2020
DOI: 10.1111/febs.15240
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage response proteins regulating mitotic cell division: double agents preserving genome stability

Abstract: The DNA damage response recognizes DNA lesions and coordinates a cell cycle arrest with the repair of the damaged DNA, or removal of the affected cells to prevent the passage of genetic alterations to the next generation. The mitotic cell division, on the other hand, is a series of processes that aims to accurately segregate the genomic material from the maternal to the two daughter cells. Despite their great importance in safeguarding genomic integrity, the DNA damage response and the mitotic cell division we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 159 publications
2
39
0
Order By: Relevance
“…It has been shown that DNA repair factors can be recruited to mitotic spindles [145,152,153] or the main microtubule organizing centers, the centrosomes [145,[154][155][156][157][158][159]. However, it remains difficult to determine whether the presence of these proteins in mitosis has an actual role in regulating microtubule stability, as experiments using protein depletion make it complicated to discern the role of these proteins in interphase and mitosis.…”
Section: Replication Stress and Spindle Microtubulesmentioning
confidence: 99%
“…It has been shown that DNA repair factors can be recruited to mitotic spindles [145,152,153] or the main microtubule organizing centers, the centrosomes [145,[154][155][156][157][158][159]. However, it remains difficult to determine whether the presence of these proteins in mitosis has an actual role in regulating microtubule stability, as experiments using protein depletion make it complicated to discern the role of these proteins in interphase and mitosis.…”
Section: Replication Stress and Spindle Microtubulesmentioning
confidence: 99%
“…It is now becoming clear that abscission is a very complex and highly regulated event ( Schiel and Prekeris, 2010 ; Addi et al, 2018 ; Fremont and Echard, 2018 ). Indeed, recent studies identified a new mitotic checkpoint, known as abscission checkpoint, that is activated by lagging chromosomes and leads to the arrest of the cells in telophase ( Sadler et al, 2018 ; Bai et al, 2020 ; Petsalaki and Zachos, 2020 ). We now know that abscission involves highly organized remodeling of the cytoskeleton at the ICB.…”
Section: Discussionmentioning
confidence: 99%
“…It is now becoming clear that abscission is a very complex and highly regulated event (Addi et al, 2018;Fremont and Echard 2018;Schiel and Prekeris 2010). Indeed, recent studies identified a new mitotic checkpoint, known as abscission checkpoint (also sometimes referred to as NoCut), that is activated by lagging chromosomes and leads to the arrest of the cells in telophase (Bai et al, 2020;Petsalaki and Zachos 2020;Sadler et al, 2018). We now know that abscission involves highly organized remodelling of the cytoskeleton at the ICB.…”
Section: Discussionmentioning
confidence: 99%